2011
DOI: 10.1373/clinchem.2011.167601
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Delayed Storage on the Measured Proteome and Metabolome of Human Cerebrospinal Fluid

Abstract: BACKGROUND Because cerebrospinal fluid (CSF) is in close contact with diseased areas in neurological disorders, it is an important source of material in the search for molecular biomarkers. However, sample handling for CSF collected from patients in a clinical setting might not always be adequate for use in proteomics and metabolomics studies. METHODS We left CSF for 0, 30, and 120 min at room temperature immediately after sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…Previous reports detected ~40–90 metabolites using GC/MS in normal human CSF [3537], and the number of metabolites identified in this study was similar to that in the previous reports. The lactic acid level in the CSF was significantly elevated in the GBMs compared with the grades I–II gliomas.…”
Section: Discussionsupporting
confidence: 89%
“…Previous reports detected ~40–90 metabolites using GC/MS in normal human CSF [3537], and the number of metabolites identified in this study was similar to that in the previous reports. The lactic acid level in the CSF was significantly elevated in the GBMs compared with the grades I–II gliomas.…”
Section: Discussionsupporting
confidence: 89%
“…First, proteomic studies require careful sample collection and storage. Prolonged contact of CSF and plasma with cellular components has been shown to affect protein and peptide quality because of the presence of proteolytic enzymes in plasma [22, 23] and CSF [24, 25]. Samples analyzed in this study were centrifuged within an hour of collection to remove all cellular components, although protease inhibitors, which can minimize degradation, were not added.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, residual enzymatic activity in refrigerated rat plasma resulted in increased levels of choline, glycerol, tyrosine, and phenylalanine [38]. In another study of the factors affecting the stability of metabolites in cerebrospinal fluid, the authors found that rapid centrifugation immediately (<5 min) after collection to remove white blood cells and snap-freezing (<2 h) were important to preserve accurate metabolite levels [39,40]. After delayed storage of 30 and 120 min, numerous metabolites (24 and 46 respectively, of a total 57 known metabolites detected) had significantly elevated levels, including glucose and ten amino acids (Thr, Glu, Gly, His, Ser, Ala, Phe, Tyr, Ile, and Asn), because of unquenched enzymatic activity, as shown in Fig.…”
Section: Importance Of Sample Preparation In Global Metabolomicsmentioning
confidence: 99%